Effect of high-intensity interval training on the skeletal muscle of spontaneously hypertensive rats - Paulo Henrique Aleixo; Robson Chacon Castoldi; Francilene Lima Agostinho De Souza; Thaoan Bruno Mariano; Guilherme Akio Tamura Ozaki; Thiago Alves Garcia; Lucas Silva Santos; Francis Lopes Pacagnelli; Regina Celi Trindade Camargo; José Carlos Silva Camargo Filho (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study aimed to evaluate the effect of High-Intensity Interval Training (HIIT) on the skeletal muscle of Spontaneously Hypertensive Rats (SHR). Method: In total, 20 male rats, SHR, 12 months old, were used, distributed into 2 groups: Control Group (C) and Training Group (HIIT). The training lasted approximately 50 minutes/day, 5 days/week, for 8 weeks. Systolic blood pressure (BP) was measured at the beginning and end of the study. Analysis: The medial gastrocnemius muscle was used to measure the smallest fiber diameter, after which the Shapiro-Wilk normality test was performed, followed by the Mann Whitney test to compare the medians and interquartile intervals (IQI) of the muscle fibers and Student t-test for performance. For analysis of BP, Analysis of Variance - ANOVA was used, followed by Tukey's post-test. All procedures adopted a significance value of 5% (p < 0.05). Results: The median values for the variable "smallest diameter" of muscle fibers were 29.48 (IQI: 9.96) µm in the C group and 33.45 (IQI: 9.44) µm in the HIIT group (p < 0.05). Also, the performance was increased in the trained animal group and blood pressure values decreased significantly at the end of the experiment (p < 0.05). Conclusion: The HIIT intensity promoted an increase in the median values of the muscle fibers and performance. Finally, a significant decrease was observed in blood pressure variation values.